Functionalized ionic liquid coatings in the Pd-catalyzed selective hydrogenation of acetylene in ethylene-rich feeds - Kremitzl, Daniel; Röhrs, Karoline; Williams, Marc B.; Schulz, Peter; Wasserscheid, Peter (Journal of Ionic Liquids, 2024)
This study explores the tuning of a Pd/Al2O3 hydrogenation catalyst for the selective removal of trace acetylene from ethylene-rich feeds by coating the catalyst with non-functionalized and functionalized ionic liquids (denoted as SCILL and Advanced SCILL materials, respectively). These materials were tested in an automated continuous hydrogenation rig converting 3300 ppm of acetylene in excess ethylene, a gas mixture mimicking a technical front-end steam cracker feed composition. While the sulfonic-acid-functionalized IL coating resulted in a highly active but very unselective catalyst converting mainly ethylene to ethane, an Advanced SCILL catalyst prepared from a nitrile-functionalized IL reduced the acetylene concentration down to less than 1 ppm, while leaving over 99% of the ethylene untouched. We also examined the potential transformations of the IL layer under reaction conditions by means of 1H NMR. Except for a ketone-functionalized IL, which was inherently labile, all tested ILs primarily underwent C2-ethylation or remained unaltered. Our findings highlight the great potential of functionalized ILs in modifying heterogeneous hydrogenation catalysts.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Acetylene; Ethane; Ethylene; Hydrogenation; Ionic liquid; Pd on alumina

Hydrogenation with Dissolved Pt-Complexes Homogenously Distributed in the Ionic Liquid or Enriched at the Gas/Ionic Liquid Interface - Khan Antara, Sharmin; Hemmeter, Daniel; Zhai, Ziwen; Kremitzl, Daniel; Maier, Florian; Koller, Thomas Manfred; Steinrück, Hans-Peter; Haumann, Marco (ChemCatChem, 2024)
The use of homogeneous catalysts dissolved in ionic liquids (ILs) is an established field of research. Thin IL films containing dissolved catalyst complexes can be immobilized on solid porous supports, thereby creating a heterogenized catalyst material. Aiming at the deliberate positioning of such supported ionic liquid phase (SILP) catalyst, we carried out investigations of two very similar Pt-complexes: depending on the ligand periphery, the first one is homogeneously dissolved in the IL while the second one strongly enriches at the gas/IL interface. To study these different locations within thick IL films of approximately 1 mm thickness, we investigated the hydrogenation of ethene in a continuous pool-reactor setup. The two complexes dissolved in the IL [C4C1Im][PF6] showed different activity which can be attributed to their different locations. At 313 K and 0.62 MPa total pressure, the surface-enriched complex was approximately two times more active. However, under these conditions the formation of Pt particles could be observed, with the surface-enriched complex exhibiting a stronger tendency for particle formation compared to the one homogeneously distributed in the IL, as derived from XPS and light-scattering measurements.
CRIS-Team Scopus Importer:2024-08-02
Keywords: ethene; Hydrogenation; interface enrichment; ionic liquid; light-scattering; platinum; XPS

Influencing the Product Distribution in Citral Hydrogenation Using Ionic Liquid Modified Cu Catalysts - Naicker, Letisha; Schörner, Markus; Kremitzl, Daniel; Friedrich, Holger B.; Haumann, Marco; Wasserscheid, Peter (ChemCatChem, 2022)
This work shows the effect of selected ionic liquids on the catalytic performance of a Cu/Al2O3 catalyst towards citral hydrogenation. The Cu/Al2O3 was prepared using a combination of wet impregnation and strong electrostatic interaction technique. The catalyst was coated with three ionic liquids, namely: [C4C1Pyrr][OTf], [C2C1C1Im][NTf2], and [C2C1Im][NTf2] resulting in Cu-based SCILL catalysts (solid catalyst with an ionic liquid layer). The fresh and used SCILL catalysts were characterized using FT-IR spectroscopy and thermal gravimetric analysis. All Cu-SCILL catalysts were stable throughout the liquid-phase reactions with no leaching of ionic liquid being detectable by means of TGA. All ionic liquids investigated prevented the formation of undesired isopulegol compared to the 30 % isopulegol selectivity obtained over the bare Cu/Al2O3 catalyst. The Cu-SCILL (coated with 15 wt% [C2C1Im][NTf2]) increased the selectivity towards geraniol and nerol by 340 %.
CRIS-Team Scopus Importer:2022-09-16
Keywords: Citral; Copper; Ionic liquid; SCILL; Selective Hydrogenation

Tailoring the Surface Enrichment of a Pt Catalyst in Ionic Liquid Solutions by Choice of the Solvent - Hemmeter, Daniel; Gezmis, Afra; Kremitzl, Daniel; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans-Peter (Advanced Materials Interfaces, 2024)
The so-called buoy-effect, that is, the targeted surface enrichment of a Pt catalyst dissolved in ionic liquids (ILs), is achieved by attaching perfluorinated alkyl chains to the ligand system, which drags the metal complex toward the interface. Using angle-resolved X-ray photoelectron spectroscopy, it is demonstrated how this surface enrichment can be tailored by variation of the solvent IL. In [CnC1Im][PF6] ILs (n = 2, 4, 8), the surface is fully saturated with the complex at 10%mol bulk content, while in [C4C1Im][Tf2N] only at 20%mol saturation is observed. At low catalyst concentrations of 1%mol, where saturation is not yet reached, the enrichment increases with decreasing length of the IL alkyl chain. As a general rule, the degree of surface enrichment decreases with the decrease in surface tension of the solvent IL, that is, in the order [C2C1Im][PF6] > [C4C1Im][PF6] > [C8C1Im][PF6] > [C4C1Im][Tf2N]. In ILs with very low surface tension, enrichment is even suppressed. These results reveal the surface tension of the solvent IL as rational parameter for tailoring the interfacial structure of IL-based catalyst systems, such as supported ionic liquid phase (SILP) catalysis, where the nature of the IL/gas interface is expected to strongly influence the performance of the process.
CRIS-Team Scopus Importer:2024-05-03
Keywords: materials properties; Pt catalyst; supported ionic liquid phase catalysis (SILP); surface enrichment; X-ray photoelectron spectrsocopy

The Buoy Effect: Surface Enrichment of a Pt Complex in IL Solution by Ligand Design - Hemmeter, Daniel; Kremitzl, Daniel; Schulz, Peter; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans-Peter (Chemistry - A European Journal, 2023)
The targeted enrichment of a Pt complex with an ionic liquid (IL)-derived ligand system in IL solution is demonstrated by using angle-resolved X-ray photoelectron spectroscopy. When the ligand system is complemented with fluorinated side chains, the complex accumulates strongly at the IL/gas interface, while in an equivalent solution of a complex without these substituents no such effect could be observed. This buoy-like behavior induces strong population of the complex at the outermost molecular layer close to surface saturation, which was studied over a range from 5 to 30 %mol. The surface enrichment was found to be most efficient at the lowest concentration, which is particularly favorable for catalytic applications such as supported ionic-liquid-phase (SILP) catalysis.
CRIS-Team Scopus Importer:2023-01-20
Keywords: catalysis; ionic liquids; surface analysis; surface enrichment; X-ray photoelectron spectroscopy (XPS)

Understanding the Buoy Effect of Surface-Enriched Pt Complexes in Ionic Liquids: A Combined ARXPS and Pendant Drop Study** - Hemmeter, Daniel; Paap, Ulrike; Wellnhofer, Nicolas; Gezmis, Emine; Kremitzl, Daniel; Wasserscheid, Peter; Steinrück, Hans-Peter; Maier, Florian (ChemPhysChem, 2023)
Recently, we demonstrated that Pt catalyst complexes dissolved in the ionic liquid (IL) [C4C1Im][PF6] can be deliberately enriched at the IL surface by introducing perfluorinated substituents, which act like buoys dragging the metal complex towards the surface. Herein, we extend our previous angle-resolved X-ray photoelectron spectroscopy (ARXPS) studies at complex concentrations between 30 and 5 %mol down to 1 %mol and present complementary surface tension pendant drop (PD) measurements under ultraclean vacuum conditions. This combination allows for connecting the microscopic information on the IL/gas interface derived from ARXPS with the macroscopic property surface tension. The surface enrichment of the Pt complexes is found to be most pronounced at 1 %mol. It also displays a strong temperature dependence, which was not observed for 5 %mol and above, where the surface is already saturated with the complex. The surface enrichment deduced from ARXPS is also reflected by the pronounced decrease in surface tension with increasing concentration of the catalyst. We furthermore observe by ARXPS and PD a much stronger surface affinity of the buoy-complex as compared to the free ligands in solution. Our results are highly interesting for an optimum design of IL-based catalyst systems with large contact areas to the surrounding reactant/product phase, such as in supported IL phase (SILP) catalysis.
CRIS-Team Scopus Importer:2023-11-10
Keywords: homogeneous catalysis; ionic liquids; surface enrichment; surface tension; X-ray photoelectron spectroscopy (XPS)